Reflective liquid crystal display without flicker for reducing eye strain. Issue 12 (28th May 2015) - Fukai, Shuji; Niikura, Yasuhiro; Ikenaga, Makoto; Hatsumi, Ryo; Nishi, Takeshi; Ishitani, Tetsuji; Hirakata, Yoshiharu; Koyama, Jun; Yamazaki, Shunpei; Sato, Rai; Cho, Takayuki
Abstract We fabricated two types of 6.05‐in. active matrix reflective liquid crystal displays (LCD) using a c‐axis‐aligned crystalline oxide semiconductor (CAAC‐OS) for the driver circuit and field‐effect transistors in pixels: one is of the high‐reflectance type, and the other is of the wide‐gamut type. Because of the small off‐state current of the CAAC‐OS and the improved liquid crystal material, low‐frequency driving at 1/60 fps or lower was achieved without memory in a pixel. Consequently, the still image display does not require data writing, except in turning pages; thus, it is flicker‐free in still image display. We also examined the page‐turning operation for less eye strain. The study shows that a reflective color LCD using a CAAC‐OS results in eye‐friendly still image display without flicker similar to an electrophoretic display (EPD); however, it is capable of moving image display, color display, and eye‐friendly page‐turning operation, which are difficult to achieve with an EPD.